Environment and time drive the links between the species richness and ecosystem multifunctionality from multitrophic freshwater mesocosms - Xu, Zhiyan; Yang, Hui; Mao, Hongzhi; Peng, Qiutong; Yang, Shiwen; Chou, Qingchuan; Yang, Yujing; Li, Zhongqiang; Wei, Lifei (Frontiers in Marine Science, 2023)
Understanding the link between biodiversity and ecosystem functioning is imperative for ecosystem-based management. The role of multitrophic diversity in sustaining multifunctionality remains unclear, especially in highly diverse aquatic ecosystems. We performed a species-addition experiment consisting of one, two, three, and five species in simulated multitrophic ecosystems to evaluate biodiversity and ecosystem functioning relationships within and across trophic levels. Our results showed that there are positive species richness–productivity relationships within and across trophic levels. We found significant negative correlations between species richness and the cumulative variation of total phosphorus, and between species richness and ecosystem multifunctionality across trophic levels. Also, we found that the relationships between ecosystem multifunctionality and species richness within and across the trophic levels are mediated by a combination of environmental factors, including water temperature, dissolved oxygen, pH, irradiance, and time, rather than by species richness. Our results imply that species richness–ecosystem functioning relationships vary for different ecological functions; the individual ecosystem functions selected and the way multifunctionality calculated are critical when examining links between biodiversity and ecosystem multifunctionality. Our study highlights that multitrophic richness, such as for consumers, is crucial for driving ecosystem multifunctionality. Furthermore, our study implies that management practices for restoring the diversity of aquatic macrophytes in wetlands should consider not only macrophyte richness but also different functional groups and life-forms.